Business Intelligence Solutions - a Way of General Improvement of Efficiency and Effectiveness - Sabina POPESCU (Revista de Management Comparat International)
Business Intelligence (BI) solutions provide organizations the opportunity to make the best decisions in order to have a better image of business environment. Today, the organizations can not focus on solving problems just at the departmental or functional level in an isolated way. An integrated knowledgebase enables at organizational level to improve access to everyday decisions. In this respect, these organizations must select BI tools, easy to use, flexible and allow the user to see different parts of the business